Nanoemulsion Fuel Additive Used as a Diesel Combustion Catalyst - Richard Hicks (Journal of Combustion)
This research article discloses how a uniquely structured fuel additive can easily be mixed with commercially available diesel fuel to produce an extremely stable nanoemulsion fuel. Even when using an ultralow dose (125 ppm), the additive still creates a large and catalytically active surface area using billions of nanosized water droplets (4 nanometers). No metallic or organometallic compounds were used. When used in heavy duty diesel engines, treated fuel significantly improves vehicle fuel economy. Extensive verification testing was carried out using multiple fleets of heavy duty diesel trucks operating for up to two years under “real-world” driving conditions. Testing used 538 heavy duty trucks and 15 different vehicle fleets. Test vehicles used 475,000 litres of treated fuel and covered a total of 14 million kilometres. Fleet testing was supervised by one of the premier European testing agencies (TNO Quality Services BV). Raw fuel economy data was collected and analyzed by an independent consulting agency andd showed a combined average weighted fuel savings of 9.7%. Diesel engine CO2 emissions are one of the many contributory causes of global warming. Unfortunately, new engine fuel economy technologies can take 10 years to have a 50% impact (typically 5% per year, as older vehicles are slowly replaced with new models). However, using the additive would immediately improve the combustion properties of fuel being used in these vehicles with the potential to reach up to 90% of the entire diesel vehicle population within about 60 days.